Vehicular impact resistance of highway bridge with seismically-designed UHPC pier. (1st February 2022) - Heng, Kai; Jia, Pengcheng; Xu, Jiapei; Li, Ruiwen; Wu, Hao
Highlights: Six types of bridge piers are designed with two concrete types and three various seismic fortification levels. Total 54 collision scenarios of heavy truck impacting on simply-supported bridge are numerically performed. Effects of seismic fortification level and concrete type of pier on bridge impact resistance are demonstrated quantitatively. A displacement-based evaluation method for the impact-resistant performance of bridge structure is proposed. Abstract: This study strives to numerically explore the performance of highway bridge supported by seismically-designed ultra-high performance concrete (UHPC) piers in resisting heavy truck impact. Firstly, six types of bridge piers are designed with considering two different concrete types (i.e., normal strength concrete (NSC) and UHPC) and three various seismic hazard levels (i.e., earthquake intensities (EI) of 7, 8, and 9) according to Chinese seismic design specifications, and the corresponding refined finite element (FE) models are established and validated by reproducing the tests of drop hammer impacting on reinforced NSC and UHPC members. Based on the well-verified FE models of simply-supported double-pier bent highway bridge and heavy truck, total 54 collision scenarios are carefully designed by referring to the actual accidents, and the vehicle-pier collision analyses are numerically performed by using the nonlinear FE analysis program LS-DYNA. Then, the effects of seismic fortification level and concrete type of impacted pier on the vehicular impact force and dynamic responses of entire bridge structure, as well as the damage and failure modes of both impacted pier and entire bridge are studied. It demonstrates the effectiveness of seismically-designed UHPC pier on improving the vehicle-impact resistance of bridge structure. Besides, more attentions should be paid to the safety of NSC-EI7 and UHPC-EI7 piers and the brittle shear failure in NSC-EI8 piers. Finally, aiming to quantitatively compare the anti-collision performances of entire bridge structure supported by NSC and UHPC piers under the identical seismic fortification intensity, a performance evaluation method of entire bridge structure is proposed based on the residual lateral displacement of the impacted pier. The present work can provide helpful references for the practical applications of UHPC in bridge piers and the on-site feasible evaluation of the residual performance of the post-collision bridge structure.